(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Simple, precise, accurate & robust RP-High pressure liquid chromatographic method is develop & validate for the quantitative analysis in Erdosteine capsule dosage form containing 300 mg of active pharmaceutical ingredient. Chromatographic process of separation is performed at C 18 Column (250 mm × 4.6 mm, 5μm) at 30°C and using an phosphate buffer mobile phase containing C7H15NaO3S & ACN (850 : 150 v / v) at flow rate of one millilitres / minutes. Detections is performed at the 220nm & the injections volume 20 μL. The ICH guidelines for Accuracy, Linearity, Precision, Specificity, and Robust are followed in validation of this approach. Erdosteine eluted at around 5.8 min and showed acceptable peak purity. Linearity was done in the concentration range 29.719 - 594.381μg/mL with correlation co-efficient (r²) of 0.9996. Method Precision for the 300 mg capsule formulation demonstrated a % RSD of 0.21 % and the intermediate precision showed % RSD values consistently not more than 1.0 %. Accuracy is verified by recovery study, with mean recoveries between 98.6 % and 99.9 %. The robustness study was carried out by changing deliberately the chromatographic conditions and no significant change of assay performance was observed. The validation method is found to be appropriate for regular quality checking and control of analysis at erdosteine in dosage form of capsules and provides a useful practical analytical method for pharmaceutical industries engaged in Erdosteine capsule manufacturing